MITIGASI BENCANA KEPARIWISATAAN - Abdul Rahman; Nizar Fredika Ardhiansyah; Hayin A Pasaribu; Rio Saputra (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2022)
Tourism is one of the crucial sectors that cannot be separated from the potential threat of disaster. To reduce these potential threats, the government through the National Disaster Management Agency and the Ministry of Tourism is carrying out a disaster-safe tourist destination program. Aik Berik Village, Batukliang Utara District as a leading tourist village in Central Lombok Regency has the responsibility to realize the government program. Starting from public awareness of the management of the Aik Berik Community Forest, then it became a progressive case as part of community-based disaster mitigation. So this study aims to determine the behavior of the people of Aik Berik Village, then analyze its effect on reducing disaster threats as an effort to create a disaster-safe tourism village. The method used is descriptive qualitative with a case study approach. The results of the study show that disaster mitigation carried out by the community through a sustainable community forest management system has been proven to be effective in reducing or even eliminating potential disaster threats in Aik Berik Village, especially at the location of village natural attractions.